DISPHEMISMS AND THEIR TRANSLATIONS IN BBC ONLINE NEWS TEXTS (DISFEMISME DAN TERJEMAHANNYA PADA TEKS BERITA BBC ONLINE) - Hanifa Pascarina (Leksema: Jurnal Bahasa dan Sastra, 2018)
This research was aimed at identifyingÂ  the uses of disfemism on BBC Online news texts at the level of grammatical units and describing their backgrounds as well as analyzing their forms and qualities of translations, particularly from the aspect of acceptability in Indonesian language. The method used for analysis was content analysis with disfemism on BBC Online news texts as the object of analysis. The data were in the forms of linguistic units of the news texts containing disfemism. The data were then analyzed by using referential comparison technique with semantic and translation approach to understand the meanings of disfemism and pragmatic comparison for analyzing the backgrounds.The results show that the grammatical units of disfemism on BBC Online news texts were at the levels words, phrases, and clauses. In addition, no significant change of form was found in the translations.There were found 10 different reasons underlying the uses of disfemism on BBC Online news texts. Meanwhile, dealing with the acceptability, most of the translations of disfemism can be counted as acceptable